Breastfeeding practices and postpartum weight retention in an Asian cohort - Loy, See Ling (2024)
This study examines relationships between breastfeeding practices and postpartum weight retention (PPWR) at 6 and 12 months postpartum among 379 first-time mothers participating in a clinical trial in Singapore. We categorized feeding modes at 6 months into exclusive breastfeeding, mixed feeding, and exclusive formula feeding. Participants were analyzed in two groups based on their PPWR assessment at 6 and 12 months postpartum, with complete datasets available for each assessment. We calculated PPWR by subtracting pre-pregnancy weight from self-reported weight at 6 and 12 months postpartum, defining substantial PPWR as ≥5 kg retention. Modified Poisson regression models adjusted for potential confounders were performed. At 6 and 12 months, 35% (n = 132/379) and 31% (n = 109/347) of women experienced substantial PPWR, respectively. Compared to exclusive breastfeeding, mixed feeding (risk ratio 1.85; 95% confidence interval 1.15, 2.99) and exclusive formula feeding (2.11; 1.32, 3.28) were associated with a higher risk of substantial PPWR at 6 months. These associations were slightly attenuated at 12 months and appeared stronger in women with pre-pregnancy overweight or obesity. This study suggests that breastfeeding by 6 months postpartum may help mitigate PPWR, particularly with exclusive breastfeeding. It also draws attention to targeted interventions to promote breastfeeding among women with overweight or obesity.